Process Standardization for the Preparation of Smoked Cubes and Fillet Steaks from a Marine Perch, Lethrinus lentjan (Lacepede 1802) - Sindhu, S; Krishnakumar, S; Nambudiri, D D; Korath, Alphi (Fishery Technology, 2025)
A study was undertaken for the preparation of smoked cubes and fillet steaks from a marine perch King emperor Lethrinus lentjan (Lacepede) and the conditions for preparation were standardized. The parameters standardized were conditions for brining, draining, predrying, smoking temperature and smoking time. Brining conditions comprised brine concentrations of 10, 15 and 20% and brining periods of 15, 30 and 45 min each. Draining at room temperature and at 10°C for 10, 20 and 30 min were studied. The pre-drying conditions selected were pre-drying in a mechanical drier and smoking kiln at 50°C for 15, 30, 45 and 60 min. Smoking conditions such as smoking at 80, 90 and 100°C for 1, 2 and 3 h each were considered. Salt, moisture and phenol content of the samples were analysed in addition to sensory analysis. Based on the test results, brining at a concentration of 10%, for 15 min, draining under refrigerated condition for 30 min, pre-drying in a mechanical drier for 30 min at 50°C and smoking at 80°C for a period of 3 h were found to be ideal. Smoked cubes and fillet steaks prepared using the standardised procedure had superior quality on sensory evaluation